Forced Remote Learning during the COVID-19 Outbreak: International Students’ Stories from a Bahasa Indonesia (the Indonesian Language) for Foreigners Classroom - Hastowohadi; Setyaningrum, Rina Wahyu; Pangesti, Fida (Journal of International Students, 2020)
The present study explores the international students’ experiences of learning the Indonesian language (bahasa Indonesia) during the COVID-19 outbreak. Five students who learned bahasa Indonesia for foreigners were recruited for this narrative research. They were from Thailand, Vietnam, Yemen, Sierra Leone, and Japan. Narrative data were collected through in-depth interviews and then analyzed using language appraisal and emotional geography theories. Findings showed that the forced remote learning affected students’ emotional conditions, such as sadness, disappointment, anxiety, and resignation which contradicted their expectations. This empirical evidence suggests a change in remote learning management by integrating a sound instructional design to create autonomous learning.